INVESTIGATIONS OF THE BINDING PARAMETRES OF THE INTERACTION OF N'-FERROCENYLMETHYL-N'-PHENYLACETO- AND PROPIONOHYDRAZIDE WITH DNA - Mouada, H; Lanez, T; Lanez, E (university of eloued -جامعة الوادي, 2019)
Herein we describe the determination of binding parameters of the interaction of N'- ferrocenylmethyl-N'-phenylacetohydrazide (FcA) and N'-ferrocenylmethyl-N'-phenylpropionohydrazide (FcP) derivatives with chicken blood double-stranded DNA (cb-ds DNA) in phosphate buffer (PB) solution at physiological pH 7.2 by electronic spectroscopy and molecular docking calculations. The results indicated that both FcA and FcP bind DNA in groove binding mode, values of binding constants and binding free energy obtained from electronic spectroscopy measurements and molecular docking calculations were in good agreement
article
Keywords: DNA, interaction, electronic spectroscopy, molecular docking